A QUALITATIVE STUDY OF BEHAVIORAL SEGMENTATION ON BLACKCUP COFFEE HOUSE MANADO - Rotinsulu, Stephen .; Lambey, Linda .; Rumokoy, Farlane S. (Universitas Sam Ratulangi, 2017)
Abstract: The objectives of this study are to identify how behavioral segmentation factors influence the segmentation of specialty coffee house market especially BlackCup Coffee House in Manado and to identify effective strategies developed by specialty coffee house business in Manado in accordance with behavioral segmentation approach. This is a qualitative study, 10 respondents were chosen by purposive sampling. They are all customers who ever visited BlackCup Coffee House Manado. The findings from this research are: Coffee houses with specialty coffee as the main product began to be the choice for many people, especially for coffee-drinkers in Manado. Also, considering the coffee house industry with specialty concept are still relatively new, then business actor should start to make this as business opportunity to specialty coffee house industry more widely known in Manado. Keywords: market segmentation, behavioral segmentation, consumer behavior, black cup.